Optimization of Health Cadres in Postpartum Maternal Management - Maryatun; Indarwati, Indarwati; Susilowati, Tri; Hermawati, Hermawati (PT Inovasi Pratama Internasional, 2024)
Training of health cadres in postpartum maternal management has a crucial role in ensuring the health and well-being of mothers after childbirth. Postpartum mothers face a variety of physical and emotional changes that require proper attention and care. The training aims to increase the knowledge of cadres in the management of postpartum mothers. The method offered is to conduct socialization and knowledge improvement training for health cadres. This training covers important aspects such as understanding of postpartum physical changes, danger signs to watch out for, providing episiotomy or cesarean wound care, pain management, promotion of breast milk, as well as communicative and empathetic approaches in providing emotional support to postpartum mothers. This training also encourages health cadres to play a role as disseminators of health information that can help postpartum mothers in making informed decisions regarding self-care and their babies. Health Cadres are able to provide accurate information and provide comprehensive initial care to postpartum mothers in the community. This training also has a positive impact in reducing the number of postpartum complications, increasing exclusive breastfeeding, and increasing awareness of postpartum mothers to danger signs that require further medical attention. Result: increased knowledge of health cadres in the management of postpartum mothers. Conclusion: this training is able to increase the knowledge of health cadres in postpartum maternal management